Examining Consumer Attitudes and Values Toward Environmentally Friendly Products: The Significance of Environmental Awareness for Today’s Consumers - Marija Jankovic; Tamara Panajotovic; Klara Djurovic (Universitas Diponegoro, 2024)
This paper examines the attitudes, opinions, and values that consumers hold regarding environmentally friendly products in the domestic market. Given the fact that consumers have been focused on sustainability and environmental consciousness more than ever, it is crucial to understand how these factors influence purchasing decisions. Special attention will be paid to the role of environmental awareness in shaping consumer attitudes and behaviors in the context of purchasing sustainable products. To collect quantitative data, a structured questionnaire will be used, while focus groups will be applied as a qualitative method to gain deeper insights into consumer attitudes and opinions. Additional data will be collected through observational studies in stores and online shopping. The research results will provide data for more precise definition of marketing strategies, adjustment of production processes to produce more environmentally friendly products, as well as for product development.